The international spillover effects of pension reform - Yvonne Adema; Lex Meijdam; Harrie A. A. Verbon (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper explores how pension reforms in countries with PAYG schemes affect countries with funded systems. We use a two-country two-period overlapping-generations model, where the countries only differ in their pension systems. We distinguish between the case where a reform potentially leads to a Pareto improvement in the PAYG country, and where this is impossible. In the latter case the funded country shares both in the costs and the benefits of the reform. However, if a Pareto-improving pension reform is feasible in the PAYG country, a Pareto improvement in the funded country is not guaranteed.
Keywords: H63; F21; F47; F41; H55; 330; international spillover effects; pension reform; Rentenreform; Umlageverfahren; Spillover-Effekt; Kapitaldeckungsverfahren; Zwei-Länder-Modell; international; Theorie